2007
DOI: 10.4319/lo.2007.52.2.0635
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term chlorophyll dataset reveals regime shift in North Sea phytoplankton biomass unconnected to nutrient levels

Abstract: During the 1980s, a rapid increase in the Phytoplankton Colour Index (PCI), a semiquantitative visual estimate of algal biomass, was observed in the North Sea as part of a regionwide regime shift. Two new data sets created from the relationship between the PCI and SeaWiFS chlorophyll a (Chl a) quantify differences in the previous and current regimes for both the anthropogenically affected coastal North Sea and the comparatively unaffected open North Sea. The new regime maintains a 13% higher Chl a concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 50 publications
3
149
3
1
Order By: Relevance
“…Some studies based on satellite and in situ time-series measurements suggest that primary production in the ocean is increasing globally (2,22). Other studies indicate a reduction in primary production in mid to low latitudes because of increasing vertical stratification (3,23) and global reductions in primary production overall.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies based on satellite and in situ time-series measurements suggest that primary production in the ocean is increasing globally (2,22). Other studies indicate a reduction in primary production in mid to low latitudes because of increasing vertical stratification (3,23) and global reductions in primary production overall.…”
Section: Discussionmentioning
confidence: 99%
“…While we do not dispute that UK and Irish records of Balearic shearwater has increased in recent years, this does not prove that the number of birds visiting the UK has increased. Following work by Bourne et al (1988) (McQuatters-Gollop et al 2007). Therefore the apparent increases could simply reflect a change in observer awareness.…”
mentioning
confidence: 99%
“…As a result, high nutrient and COD concentrations are still found near its estuary, even though the river has been dammed. In most marine environments, nitrogen appears to be the limiting factor of primary production; accordingly, the concentration of TIN, PO 4 -P and molar N/P ratio can control the pattern and function of the ecosystem of a bay, as well as alter the structure, production, and biomass of phytoplankton (Balode et al, 1998;Lenton and Watso, 2000;Leonardos and Geider, 2004;McQuatters-Gollop et al, 2007). However, more N than P entered Sishili Bay from terrestrial sources during rainfall events, as indicated by the increasing trend of TIN concentrations during precipitation.…”
Section: Ecological Status During Red Tides Periodsmentioning
confidence: 99%
“…However, phytoplankton blooms can be influenced by other factors in addition to nutrient concentrations, such as sea surface temperature (McQuatters-Gollop et al, 2007;Loebl et al, 2008). In Sishili Bay, the changing trend of chl-a lagged behind that of water temperature by one month, except in 2007, showing that high water temperature tends to increase the concentration of chl-a.…”
Section: Ecological Status During Red Tides Periodsmentioning
confidence: 99%